Phase Transitions, Phase Coexistence, and Piezoelectric Switching Behavior in Highly Strained BiFeO3 Films. (12th July 2013) - Beekman, C.; Siemons, W.; Ward, T. Z.; Chi, M.; Howe, J.; Biegalski, M. D.; Balke, N.; Maksymovych, P.; Farrar, A. K.; Romero, J. B.; Gao, P.; Pan, X. Q.; et al.
<x xml:space="preserve">Abstract</x> Highly strained BiFeO3 films transition into a true tetragonal state at 430 °C but remain polar to much higher temperatures (∼800 °C). Piezoelectric switching is only possible up to 300 °C, i.e., at temperatures for which strain stabilizes the stripe‐like coexistence of multiple polymorphs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>